1999
DOI: 10.1007/bf02482234
|View full text |Cite
|
Sign up to set email alerts
|

Importance of positive peritoneal lavage cytology findings in the stage grouping of gastric cancer

Abstract: Although peritoneal lavage cytology is widely performed during surgery for gastric cancer and the results have been reported to be one of the accurate prognostic factors, the cancer stage is determined independent of the results of lavage cytology according to the First English Edition of Japanese Classification of Gastric Carcinoma. In this study we demonstrated the validity of lavage cytology for accurately staging gastric cancer. Between 1988 and 1996, peritoneal lavage cytology was performed in 347 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
3
13
1
1
Order By: Relevance
“…Similarly, other reports found nodal involvement to be associated with a high incidence of positive cytology [2,10,25], and a statistically significant association was found between positive cytology and advanced stage cancer [1][2][3]7,10,25,26]. Although some previous reports confirmed the association found in this study between poor tumor differentiation and positive PWC [3,7], others found no such association [17,24].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, other reports found nodal involvement to be associated with a high incidence of positive cytology [2,10,25], and a statistically significant association was found between positive cytology and advanced stage cancer [1][2][3]7,10,25,26]. Although some previous reports confirmed the association found in this study between poor tumor differentiation and positive PWC [3,7], others found no such association [17,24].…”
Section: Discussionsupporting
confidence: 79%
“…Multivariable Cox regression found PWC to be one of the most significant independent predictors of survival. Positive PWC as an independent predictor of survival has been previously reported by many investigators [2,3,6,[8][9][10][11][12][13][14]24] with a mean survival time of 8.6-18.4 months [1,7,8,17,20,24,32]. However, the influence of positive PWC on the survival of patients with gastric cancer has not been consistent.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the mechanism of peritoneal dissemination has not yet been clearly defined so far. Free cancer cells exfoliated from cancer lesions have been postulated as the main cause of metastasis [5,[8][9][10] . Recent advances on the molecular mechanisms of peritoneal dissemination have elucidated some of the target molecules and the development of new multimodal therapies in an attempt to eliminate peritoneal exfoliated www.wjgnet.com free cancer cells has also improved survival [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, cytologic examination of lavage fluid obtained at the time of surgery is a conventional method for detecting free cancer cells in peritoneal space. However, the sensitivity of this assay has been reported to be relatively low, ranging from 19% to 30% in gastric cancer invading the serosa [6][7][8][9] . As a result, some patients with negative cytology have nevertheless developed peritoneal recurrence.…”
Section: Introductionmentioning
confidence: 99%